PENGARUH VARIABEL MAKROEKONOMI TERHADAP INDEKS SAHAM SYARIAH INDONESIA (ISSI) PADA TAHUN 2011-2022 - Maulida Azzahra, Lailatul; Andni, Riyan (Journal of Sharia Economics, 2024)
This research was motivated by the inconsistent relationship between the Indonesian Sharia Stock Index (ISSI) and macroeconomic variables that influence Indonesian sharia stock prices including the inflation rate, Bi Rate, rupiah exchange rate, world oil prices, gold prices, and economic growth. The research aims to analyze, determine and explain the impact of the Indonesian Sharia Stock Index on macroeconomic variables. This type of research uses quantitative data for the period 2011 to 2022 sourced from BPS, Investing.com, BI and OJK. Data analysis techniques involve multiple linear regression tests, classical assumption tests, and hypothesis tests. The indicator achievement results describe macroeconomic variables, namely Bi Rate has a significant negative impact, the rupiah exchange rate tends to be positive and significant, and economic growth has a significant positive impact, while inflation, world oil prices and gold prices have no impact and are not significant, meaning that the Indonesian ISSI sharia stock price experiences Volatility is not fully influenced by macroeconomics, especially Bi Rate, Rupiah exchange rate, and economic growth, which means these variables contribute to the movement of Indonesian Sharia stock prices (ISSI) so that research refers to policymakers, stakeholders and investors who can consider factors fundamentally. as well as analytics in decision making and portfolio management in the Indonesian sharia stock market.